INFLUENCE OF THE TYPE OF PLASTIC MULCH AND FERTILIZER OF CHICKEN MANURE ON GROWT AND YIELD OF SHALLOT PLANTS ON ALLUVIAL SOILS - ABSAH, ABSAH; ZULFITA, DWI; BANDEM, PUTU DUPA (Jurnal Sains Pertanian Equator, 2019)
This study aims to determine the type of plastic mulch and the best dose of chicken manure fertilizer for the growth and yield of the shallot crops on the alluvial soil. This research was carried out in the street of Ampera Pontianak, in march to may 2018. The research method used a Split plot design with tho factors, namely the type of plastic mulch (black silver plastic mulch, transparent plastic mulch) and chicken manure (1000 g/plot, 2000 g/plot, 3000 g/plot). Parameters obesrved were plant height, number of leaves, leaf chlorophyll, number of tubers per clump, fresh weight of tubers per clump and dry weight of tubers per clump, then results showed that the type of plastic mulch had no significant effeect on all observation parameters. Chicken manure fertilizer has a significant effect on leaf,chloropyill. There was an interraction between the typemof plastic mulch and chicken manure against the number of tubers per clump. Keywords : shallot, types of palstic mulch, chicken manure